2015
DOI: 10.1371/journal.pone.0128013
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase Regulates the Cell Surface Proteome and Integrin Membrane Traffic

Abstract: The cell surface proteome controls numerous cellular functions including cell migration and adhesion, intercellular communication and nutrient uptake. Cell surface proteins are controlled by acute changes in protein abundance at the plasma membrane through regulation of endocytosis and recycling (endomembrane traffic). Many cellular signals regulate endomembrane traffic, including metabolic signaling; however, the extent to which the cell surface proteome is controlled by acute regulation of endomembrane traff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(121 citation statements)
references
References 81 publications
9
87
0
Order By: Relevance
“…, 2012) by manually delineating a region of interest corresponding to the cell outline, followed by measurement of the mean pixel intensity within this region (Ross et al. , 2015) for each of the TIRF-M and epifluorescence channels for each cell.…”
Section: Methodsmentioning
confidence: 99%
“…, 2012) by manually delineating a region of interest corresponding to the cell outline, followed by measurement of the mean pixel intensity within this region (Ross et al. , 2015) for each of the TIRF-M and epifluorescence channels for each cell.…”
Section: Methodsmentioning
confidence: 99%
“…While AMPK has many targets that regulate a broad range of cellular processes, some are proteins that either modulate or undergo endocytic traffic. We previously uncovered that AMPK activation leads to broad yet specific changes to the cell surface proteome in epithelial cells, suggesting that AMPK may broadly control endocytic membrane traffic (Figure ). Indeed, AMPK regulates specific activities like glucose transport and broader processes like cell migration, as we examine next.…”
Section: Control Of Endocytic Membrane Traffic By Ampkmentioning
confidence: 98%
“…Although the importance of AMPK in trophoblast cell differentiation and in placental abnormalities has recently become evident (Carey et al, ), the role of AMPK in trophoblast cell migration and invasion has yet to be examined. Nevertheless, AMPK cell signalling is known to alter cell migration and invasion in other cell types, including endothelial cells and tumour cells (Kaiser et al, ; Vincent et al, ), and also regulates the expression of cell surface proteins involved in cell motility (Ross et al, ). Furthermore, a study using chemical genetic screening of whole cells revealed that many AMPK substrates have known roles in cell motility, adhesion, and invasion (Schaffer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of V . angustifolium on AMPK signalling in placental trophoblast cells have not yet been studied, it is important to note that AMPK has been identified as a key regulator of cell migration, invasion, and adhesion in other cell types (Kaiser, Friedrich, Chavakis, Böhm, & Friedrich, ; Ross et al, ; Schaffer et al, ; Vincent et al, ). It was therefore hypothesized that V .…”
Section: Introductionmentioning
confidence: 99%